2012
DOI: 10.3846/13923730.2012.734850
|View full text |Cite
|
Sign up to set email alerts
|

Ssi and Sssi Effects in Seismic Analysis of Twin Buildings: Discrete Model Concept

Abstract: This paper presents a numerical study of soil-structure interaction (SSI) and structure-soil-structure interaction (SSSI) effects on response of twin buildings during earthquake excitations. The buildings are modeled as shear buildings and the soil is simulated by a discrete model representing a visco-elastic half-space subjected to earthquake acceleration. Equation of motion of twin buildings with different conditions, fixed based (FB), SSI and SSSI, are developed via an analytical procedure and solved numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Mulliken and Karabalis [5] evidenced large differences in the response of three adjacent buildings founded on rigid, surface foundations with respect to the single case, by defining a simple discrete model for predicting the dynamic interaction. Effects of both soil-structure interaction and structure-soil-structure interaction were investigated by Naserkhaki and Pourmohammad [6] on response of twin buildings during earthquake excitations. A recent review of the structure-soilstructure interaction problem can be found in Menglin et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mulliken and Karabalis [5] evidenced large differences in the response of three adjacent buildings founded on rigid, surface foundations with respect to the single case, by defining a simple discrete model for predicting the dynamic interaction. Effects of both soil-structure interaction and structure-soil-structure interaction were investigated by Naserkhaki and Pourmohammad [6] on response of twin buildings during earthquake excitations. A recent review of the structure-soilstructure interaction problem can be found in Menglin et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mass ratio (ψ = mass adjacent /mass reference ) and height ratio (χ = h adjacent /h reference ) between adjacent and reference buildings are influential factors controlling SSSI phenomena [16][17][18]30,32]. In this study, to explore the effects of mass between adjacent buildings on SSSI phenomena, the mass of S1, the most massive structure, was pre-designed to be approximately 1.5 times larger than the mass of S2 and 15.3 times larger than that of S3.…”
Section: S1 S2 S3mentioning
confidence: 99%
“…Previous investigations have reported that significant changes of the near-field motion, due to the dynamic response of structures [14]. Such changes also affect the response of structures located nearby, this is called the structure-soil-structure interaction (SSSI) phenomenon [4,[15][16][17][18][19]. Therefore, it is essential in engineering practices to explore SSSI effects to avoid unexpected damage in structure when another structure is placed nearby, as SSSI effects are not considered in modern seismic design codes [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Alexander et al [15] applied this method to study SSSI effect. After that, Naserkhaki and Pourmohammad [16] probed into the work of Mulliken et al [14].…”
Section: Introductionmentioning
confidence: 99%